Dysbiosis of Cervical and Vaginal Microbiota Associated With Cervical Intraepithelial Neoplasia - Lin, Suibin; Zhang, Bin; Lin, Yixia; Lin, Yueping; Zuo, Xiaoyu (Frontiers in Cellular and Infection Microbiology, 2022)
Cervical intraepithelial neoplasia (CIN) is a precancerous condition inducing local lesions on the surface of the squamocolumnar junction of the cervix. Despite the role of vaginal microbiota having been under-discussed, the role of the cervical microbiome and the microbial migration across the reproductive tract involved in CIN was limitedly studied. We aimed to synchronously characterize the dysbiosis associated with CIN in both the cervix and vagina in a Chinese population. Profiling of cervical and vaginal microbiota from 60 CIN women and 60 healthy women was conducted. 16S rRNA sequencing was adopted. By comparing the microbial profiles between different parts of the reproductive tract, our results demonstrated an increased shift of microbial diversity in the cervix compared with that in the vagina for the CIN patients, specifically in CIN 1. Less dysbiosis was found between the CIN patients and controls, in either the vagina or cervix. The microbial community may be modulated by the onset of sexual activity, a known clinical risk factor for cervical neoplasia. Distinct patterns of perturbated bacteria were found in the vaginal and cervical microbiota, in which reduced Actinobacteria-related operational taxonomic units (OTUs) and increased Proteobacteria-related OTUs were found in the vagina and cervix, respectively. A good agreement between the direction of the top-significant perturbated OTUs was observed between the vaginal and cervical microbiome, suggesting a potential microbial migration in the reproductive tract. Enriched genera such as Sphingomonas and Stenotrophomonas were found in cervical microbiota-associated CIN. Multivariate analysis revealed Comamonas, Rhizobium, and Pseudomonas as independent genera contributing to CIN in the cervix. In summary, this study revealed the perturbation of microbiota in the presence of CIN and demonstrated a distinct pattern of characteristic bacteria community between the vagina and cervix involved in the development of CIN.